RESEARCH ON POSSIBILITIES TO IMPROVE DIESEL LOCOMOTIVES’ MAINTENANCE SYSTEM - Bureika, Gintautas (Science and Transport Progress, 2007)
The analysis of failures of the locomotive’s units and parts is presented. The reliability indicators of these parts were determined according to the locomotive run. Numerical and distribution functions describing mileage (run) of the locomotives between overhauls were also defined. The dependence of the flow of failures on mileage distribution between overhauls was determined and the optimal mileage was calculated. Methods of determining mileage based on parametric and non-parametric reliability are presented. These methods help to reduce maintenance and repair costs as well as idle time of locomotives. They also help to increase reliability. The methods suggested in the paper were used in calculating optimal mileage (run) for the locomotives of the company ‘Lithuanian Railways’.